Political parties and network formation - Topi Miettinen; Panu Poutvaara (Institute for the Study of Labor (IZA), 2006)
We argue that anti-corruption laws may provide an efficiency rationale for why political parties should meddle in the distribution of political nominations and government contracts. Anti-corruption laws forbid trade in spoils that politicians distribute. However, citizens may pay for gaining access to politicians and, thereby, to become potential candidates for nominations. Such rent-seeking results in excessive network formation. Political parties may reduce wasteful network formation, thanks to their ability to enter into exclusive membership contracts. This holds even though anti-corruption laws also bind political parties.
Keywords: D72; D85; L14; 330; political parties; two-sided platforms; network formation; Patronage; Rent Seeking; Politische Partei; Klubtheorie; Theorie